Reply to discussion on the article “Remarks on the Permian- Triassic transition in Central and Eastern Lombardy (Southern Alps, Italy)” by G. Cassinis, M. Durand and A. Ronchi - Durand, M.; Cassinis, G.; Ronchi, A. (Journal of Iberian Geology, 2009)
Sin resumen